STABILITY OF WHEAT GENOTYPES ADAPTED IN TROPICAL MEDIUM AND LOWLAND - Sumeru Ashari; Budi Waluyo; Izmi Yulianah; Niken Kendarini; Mohammad Jusuf (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2012)
The research objective was to select wheat genotypes that can adapt on the medium and low plains. Twenty-seven genotypes and three varieties of wheat were grown in four locations in the medium and low plains since June-October 2009. The experiments were arranged using a randomized complete block design repeated three times. Analysis of variance performed at each location followed by a test of homogeneity of error range, the combined analysis of variance and yields stability analysis. Genotype x environment interaction significantly affecting yield. Stable genotypes and widely adaptable across locations were G-1 (1.94 t.ha-1), G-20 (1.24 t.ha-1), H-14 (1.85 t.ha-1), H-19 (1.59 t.ha-1), H-20 (1.69 t.ha-1), H-21 (1.48 t.ha-1), 162 (1.62 t.ha-1), 80 (1.63 t.ha-1), 82 (1.78 t.ha-1), 91 (1.49 t.ha-1), and 142 (1.45 t.ha-1). Genotypes adapted in productive environment were G-18 (1.23 t.ha-1), G-19 (1.63 t.ha-1), 185 (1.30 t.ha-1), 40 (1.33 t.ha-1) and 42 (1.52 t.ha-1). Genotypes adapted in marginal environments were 28 (2,22 t.ha-1), H-1 (1.61 t.ha-1), H-8 (1.65 t.ha-1) and H-16 (1.68 t.ha-1). Genotype was selected as an improvement material in the wheat breeding in medium and lowland of tropical regions. Keywords: wheat selection, tropical, yield stability and adaptability